Mediation Agreement in A Contested Divorce Case in Cibinong District Court - Permata, Cindy; Surahmad, Surahmad (Universitas Islam Sultan Agung, 2024)
This research aims to analyze the consideration of amicable agreements in the mediation process in cases of contested divorce at the Cibinong District Court and identify the factors that influence the success and failure of mediation. As an alternative dispute resolution method, mediation has a strategic role in creating more humane and sustainable solutions. The results showed that amicable agreements in mediation are based on the principles of justice and benefit, which provide solutions more quickly, flexibly, and reduce emotional conflict compared to the litigation process. Mediation is an effective alternative for resolving disputes in divorce cases, especially regarding sensitive issues such as child custody and division of joint property. The success of mediation is influenced by several key factors, including the willingness of both parties to compromise, the competence of the mediator, and a conducive mediation atmosphere. The professionalism of the mediator is crucial to the success of this process, as they act as a neutral facilitator who helps the parties find a common solution. On the other hand, mediation failure is often caused by high emotional conflict, distrust, lack of commitment to resolve the dispute, and the absence of one of the parties. This study concludes that mediation can be an effective instrument in resolving divorce cases when supported by good communication, the commitment of the parties, and the support of a professional mediator. These findings make an important contribution to understanding the importance of strengthening the mediation process to improve the efficiency of the justice system and reduce the negative impact of divorce.